2020
DOI: 10.7759/cureus.10956
|View full text |Cite
|
Sign up to set email alerts
|

Role of Low Molecular Weight Heparin in the Management of Unexplained Recurrent Pregnancy Loss: A Review of Literature

Abstract: Recurrent pregnancy loss remains a significant challenge in gynecological practice, accounting for about 2%-4% of pregnancies. In some patients, the etiology is unknown. Unexplained recurrent pregnancy loss (URPL) refers to the spontaneous loss of three or more consecutive pregnancies without an identifiable risk factor, accounting for about 40%-50% of pregnancy losses. The review aims to understand the role of low molecular weight heparin (LMWH) in the treatment of URPL. Articles for this review have been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Low-molecular-weight heparin (LMWH) has both anticoagulant and anti-inflammatory effects. It is widely used in the treatment of recurrent pregnancy loss when used alone or in combination with other agents such as acetylsalicylic acid ( 7 , 8 , 9 ) . In many studies, it has been determined that LMWH shows positive results in live births and reduces complications such as preeclampsia and preterm birth ( 10 , 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular-weight heparin (LMWH) has both anticoagulant and anti-inflammatory effects. It is widely used in the treatment of recurrent pregnancy loss when used alone or in combination with other agents such as acetylsalicylic acid ( 7 , 8 , 9 ) . In many studies, it has been determined that LMWH shows positive results in live births and reduces complications such as preeclampsia and preterm birth ( 10 , 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic chromosomal abnormality is the main cause of spontaneous abortion in early pregnancy, which results in over 50% of rst trimester miscarriages [6][7][8]. However, there exist approximately 50% of RSA cases with unexplained recurrent spontaneous abortion [9]. RSA seriously poses threat to the life and health of pregnant women, increasing the burden on families and society.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic chromosomal abnormalities are a major cause of spontaneous abortion during the first trimester; multiple studies have shown that at least 50% of first trimester miscarriages are associated with embryonic chromosomal abnormalities (8)(9)(10). However, there remain 40% to 50% of patients with unexplainable miscarriage, referred to as unexplained recurrent spontaneous abortion (URSA) (11). Previous studies have suggested that RSA may be associated with uncharacteristic chromosomal microstructure, gene expression, and noncoding RNA expression variation (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%